2011
DOI: 10.1038/ncomms1265
|View full text |Cite
|
Sign up to set email alerts
|

The global distribution of the Duffy blood group

Abstract: Blood group variants are characteristic of population groups, and can show conspicuous geographic patterns. Interest in the global prevalence of the Duffy blood group variants is multidisciplinary, but of particular importance to malariologists due to the resistance generally conferred by the Duffy-negative phenotype against Plasmodium vivax infection. Here we collate an extensive geo-database of surveys, forming the evidence-base for a multi-locus Bayesian geostatistical model to generate global frequency map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
323
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(347 citation statements)
references
References 44 publications
16
323
3
5
Order By: Relevance
“…We observe broad consistency between the geographic distribution of the major allelic types in our dataset and previously published results [4] (Fig 1, S2 Table). We find that the FY Ã O mutation is at or near fixation in western and central African populations, but almost absent from European and Asian samples.…”
Section: Population Genetics Of the Duffy Locussupporting
confidence: 88%
See 3 more Smart Citations
“…We observe broad consistency between the geographic distribution of the major allelic types in our dataset and previously published results [4] (Fig 1, S2 Table). We find that the FY Ã O mutation is at or near fixation in western and central African populations, but almost absent from European and Asian samples.…”
Section: Population Genetics Of the Duffy Locussupporting
confidence: 88%
“…FY Ã A is defined by a derived non-synonymous mutation (D42G, rs12075) in the P. vivax binding region of the DARC protein. It is the most prevalent of the three alleles in modern human populations, with highest frequency in Asia (predicted frequency >80%) and at 30-50% frequency in Europe [4]. FY Ã A is also present in southern Africa, despite absence from western and central Africa [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…vivax is considered to be virtually absent in humans in West and Central Africa, where more than 95% of the human population is supposed to be resistant to it because of the absence of the Duffy antigen (Duffy negativity) on the surface of their red blood cells (6). However, there are several reports of Duffy positive travelers returning from these regions of the world infected with P. vivax (7)(8)(9)(10) and other studies have reported findings that suggest a possible transmission of the parasite in this region (11,12).…”
mentioning
confidence: 99%